Faktor-Faktor Yang Mempengaruhi Kesediaan Untuk Melakukan Tes Skrining Pranikah Diantara Calon Pasangan Suami Istri - Maya Sari, Puspita; Sunarsih; Neneng Siti Latifah; Ledy Octaviani Iqmy (JURNAL PROTEKSI KESEHATAN, 2025)
Premarital screening checkup is a series of tests that couples must undergo before getting married. Prospective brides and grooms need to prepare reproductive health for both prospective brides and grooms, so that after marriage they can have good health status in order to produce a quality generation. Objective: To identify the factors that influence the willingness to undergo premarital screening tests among prospective married couples. Quantitative research type with a cross-sectional approach. The population of this study was prospective married couples at the Gayabaru Health Center, Central Lampung Regency, the sample used was 73 respondents with an accidental sampling technique. The study was conducted in May-June 2024. Data collection using questionnaire sheets, bivariate data analysis (chi square). The univariate analysis of 73 respondents showed that 50 respondents (68.5%) had good knowledge, 39 respondents (53.4%) had a positive attitude, and 64 respondents (87.7%) had no family relationship.The bivariate analysis revealed that knowledge (p-value = 0.001), attitude (p-value = 0.001), and family relationship (p-value = 0.025) were statistically significant, as the p-values were less than α = 0.05 (Ha accepted and Ho rejected). There is a relationship between knowledge, attitude and kinship on the willingness to take premarital screening tests.